Pemberdayaan Keluarga Melalui Family Class dalam PengambilanKeputusan Kegawatdaruratan Ibu: Suatu Scoping Review - Juariah Juariah (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : The Minimum Service Standards (SPM) in the health sector serve as key performance indicators for local governments in ensuring the community’s right to quality health services. Regular evaluation of SPM achievements is essential to assess the effectiveness of program implementation and improvements in public health status. Objective : This study aims to describe the achievement of health SPM across 26 Community Health Centers (Puskesmas) in Samarinda City during the 2022–2024 period Research Methods/ Implementation Methods : This research employed a quantitative descriptive design using secondary data from the SPM achievement reports of the Samarinda City Health Office. Data were analyzed based on the average achievement of each Puskesmas, then aggregated to calculate the city’s average achievement per year to identify trends from 2022 to 2024. Results : : The average SPM achievement in Samarinda City was 83.75% in 2022, increasing to 93.65% in 2023, and slightly declining to 90.77% in 2024. Overall, there was a 9.9% increase from 2022 to 2023, followed by a 2.9% decrease in 2024 compared to the previous year Conclusion/Lesson Learned : The health SPM achievement in Samarinda City showed an overall upward trend over the three-year period, despite a slight decline in 2024. Evaluation of factors contributing to fluctuations, particularly in indicators with lower scores, is necessary to maintain continuous improvement in the quality of basic health services.